EXPRESSION OF THE MEANING OF ACTION TEMPORAL LOCALISATION/NON-LOCALIZATION IN THE UTTERANCE WITH SUBORDINATE CLAUSE OF TIME - Аlexandra А. Agapitova (Advanced Engineering Research, 2010)
A subordinate clause of time is considered as a way of rendering the meaning of action temporal localization/non-localization. temporal localization/non-localization meaning is conditioned by the semantics of the conjunctions of the subordinate clause of time. It is proved by the complex methodology of the text semantic interpretation.